Hard and soft skills requested by the business sector from Financial Engineering professionals - Ruiz Andia, Rodrigo; Fernández-Daza , Virginia Mercedes; Fernandez-Arraya, Victor Hugo; Quispe-Oros, Naomi Ariana (YUYAY: Estrategias, Metodologías & Didácticas Educativas, 2025)
The research focuses on the hard and soft skills demanded by the business sector from Financial Engineering professionals, aiming to identify strengths and suggestions from employers for recent graduates in this field. A descriptive study was used to analyze the skills demanded by the business sector. Surveys were conducted with both corporate sector entrepreneurs and financial entities in Bolivia. Employers value skills such as business management, financial analysis, and technological knowledge including Python and SQL. The most demanded positions include financial analyst, financial consultant, and financial risk officer, as experience is essential for these roles. Regarding academic qualifications for managerial positions, a master’s degree is required, while a bachelor’s degree or diploma may suffice for specific roles. The business sector seeks Financial Engineering professionals with a balanced combination of hard and soft skills. Among the most requested soft skills are leadership, proactivity, and creativity, along with critical thinking and teamwork ability. On the other hand, experience is considered fundamental among the most valued hard skills by employers. To enhance professionals’ performance in this field, they recommend implementing specializations in software management, financial platforms, complementary courses, and updates in the curriculum.